The role of fast processes in vacuum breakdown; Proceedings of the Xth International Conference on Phenomena in Ionized Gases, Oxford, september 13-18, 1971; Pt. 2 - Mesyats G. A. Gennady Andreyevich (1971, 1971)
В фонде НТБ ТПУ отсутствует